Genetic Variation Analysis of Hsp101 Gene in Common Wild Rice and Asian Cultivated Rice Germplasm Resources - Yue LIU; Liqun JIANG; Shuwei LYU; Bingrui SUN; Chen LI; Qing LIU; Hang YU (Guangdong nongye kexue)
【Objective】The Hsp101 gene is a key gene that regulating rice heat tolerance, however, limited knowledge is available about its genetic variation and evolutionary patterns in rice germplasm resources. The study aims to investigate the genetic variation of the Hsp101 gene in common wild rice and Asian cultivated rice, laying a foundation for the exploration of gene resources with excellent heat tolerance.【Methods】The rice germplasm resources of 3 325 genome sequencing data were obtained through retrieval and collation, and single nucleotide polymorphism (SNP) and small fragment insertion and deletion (InDel) variations were revealed by genome resequencing data analysis. Genetic diversity and gene variation haplotype analysis of the Hsp101 gene was conducted base on these genetic variations.【Results】A total of 471 genetic mutations were identified in the region of the Hsp101 gene, among which 94 non-synonymous variation sites resulted in amino acid coding changes. The analysis of genetic diversity and inter-population differentiation index showed that the genetic diversity of cultivated rice was significantly lower, and the genetic differentiation between common wild rice and Xian / Geng rice was obvious. Eight major haplotypes were identified, through haplotype analysis, with Hap1 being predominant in indica rice and Hap2 being predominant in japonica rice (7 haplotypes were found in common wild rice, except for Hap6). Further analyses including haplotype network analysis and phylogenetic analysis indicated that the wide rice haplotype Hap8 may be the oldest allele of the Hsp101 gene. In addition, three Xian or Geng rice specific variations were validated by using PCR amplification and Sanger sequencing. It was found that the specific variation of Hsp101 gene existed in Xian rice and Geng rice.【Conclusion】A total of 94 nonsynonymous variants and 8 major genetic variation haplotypes were identified in the Hsp101 gene. Hsp101 gene haplotypes of cultivated rice were evolved from those found in wild rice, and a lower degree of differentiation was observed between Xian and wild rice compared with Geng rice. It was speculated that the genetic differentiation time of Xian rice was earlier than that of Geng rice, and the genetic differences between Xian rice and Geng rice at the Hsp101 locus may be associated with the natural heat stress of their respective ecological environments.